Global research progress of visceral hypersensitivity and irritable bowel syndrome: bibliometrics and visualized analysis - Tian, Siyu; Zhang, Hang; Chen, Siqi; Wu, Pengning; Chen, Min (Frontiers in Pharmacology, 2023)
Irritable bowel syndrome (IBS) is a functional gastrointestinal disease whose pathogenesis is unknown. Many studies have found a link between visceral hypersensitivity and IBS occurrence. However, studies in this field have not been thoroughly examined using bibliometrics and visualization analysis. As a result, we obtained 974 publications from the Web of Science Core Collection (Woscc) related to IBS and visceral hypersensitivity to analyze their research hotspots and trends. CiteSpace.6.1.R2 and Vosviewer 1.6.17 were used to perform bibliometric analysis on countries, institutions, authors, highly cited references, co-cited references, and keywords in the field of study. The findings show that the number of publications has been steadily increasing over the last decade. China, the University of Oklahoma, and Simren and Magnus are the countries, institutions, and authors who have contributed the most publications, in that order. Keywords and co-citation reference analysis show that the mechanism of IBS and visceral hypersensitivity is still the focus of this research field in recent years. Future research will focus on the physiological and pathological mechanisms of IBS and visceral hypersensitivity (including mast cells, the intestinal mucosal barrier, protease activity, TRPV1, and others). This study discovered that intestinal flora may be linked to the occurrence of visceral hypersensitivity, and probiotics may be a new treatment for visceral hypersensitivity and pain. It is the first bibliometric and visual analysis of IBS and visceral hypersensitivity.